REFORMULASI PEMANFAATAN BARANG GADAI PERSPEKTIF HUKUM ISLAM - Abdul Wasik; Imam Fawaid (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
Pawnshop’s motto is to solve the problem without any problems that should be upheld as a form of social interaction in the field of Muamalah.But the reality in the society,mortgageis at issue by priests of Islamic sects because that is opposed the concept of Islam that has been previously codified. On the other hand, some scholars of Islam say that Mortgagor(Murtahin)have no right to exploit and use thegoodsthat pawned, and on the other handthere is the process of massive poverty in the society, especially forPledgor (Rohin). Therefore, the middle ground in this issue is the changing mindset of the public in understanding the meaning and the purpose ofmortgage and reformulate that utilization in accordance with Islamic law